Threshold and its performance in urban settlement - Harani, A R; Atmodiwirjo, P; Yatmo, Y A (ASCEE, 2022)
This study aims to investigate several elements as a form of threshold in the urban settlement. Threshold has the function of connectedness and separation, which is an integral part of spatial practice in urban settlements. That is how humans have the freedom to regulate their activities and space by using the threshold as connector or separator. In particular, this paper describes the elements function as a threshold for different conditions to connect and separate human roles and activities. The extent to which activities occur in a particular space and time in urban settlements is the key to determining the shape of the threshold. This paper presents an overview of the forms and performance of threshold that exist in urban settlements based on everyday practices. It not only discusses the function of elements as a threshold but also reveals the relationship between in-out of the everyday practice in urban settlements. The presence of thresholds in urban settlements is not only limited to physical elements. In this paper, we argue that the threshold element can produce a different performance due to the interacting activities between space and time. So that the understanding that connecting and separating cannot be seen as something fixed, but depends on other aspects that occur in everyday practice. This paper provides another understanding of the performance of thresholds in urban settlements, and this can be carried out in the development of a dynamic and transformative urban spatial design.